Leave no trace nightingale murder - Roland, Dan; Vincent, Bosie (Australia : BBC, 2006)
The murder of 55-year-old Cecilia Nightingale sent shock waves through the beautiful university city of Oxford. It seemed to be a motiveless killing but Police and Forensic Alliance scientists were able to piece together just what had happened and who was responsible. With access to CCTV footage and interviews with family members in Nightingale Murder, Professor of Criminology, David Wilson, investigates this astonishing case that not only resulted in a conviction but also brought together the victim's sister and the daughter of the killer.
Title from title screen
Executive producer, Nick Southgate
DVD format
Keywords: Forensic sciences; Crime scenes; Criminal investigation